2016
DOI: 10.1017/s1751731115002311
|View full text |Cite
|
Sign up to set email alerts
|

Does the effect of pelleting depend on the wheat sample when fed to chickens?

Abstract: Experimental comparisons of the nutritional value of different wheat cultivars commonly use feeds in meal form even though the largescale broiler producers use steam pelleted feeds. The aim of this experiment was to examine the effect of steam pelleting on the performance, dietary N-corrected apparent metabolisable energy (AMEn), total tract dry matter retention (DMR), nitrogen retention (NR) and fat digestibility (FD) coefficients, and digestive tract development of broilers fed four different wheat samples i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The mean average weight of birds reared at the standard temperature at 28d of age was 1196 g; which is 27.5 % below the Ross 308 broiler target weight for commercial flocks. The birds were kept in small groups in research facilities, and fed mash diets which were further mixed before feeding, potentially compromising diet homogeneity, thus the reduced performance compared to large commercial flocks was acceptable (Pirgozliev et al, 2016;Yang et al, 2020). It is possible that lighter birds may be less susceptible to heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…The mean average weight of birds reared at the standard temperature at 28d of age was 1196 g; which is 27.5 % below the Ross 308 broiler target weight for commercial flocks. The birds were kept in small groups in research facilities, and fed mash diets which were further mixed before feeding, potentially compromising diet homogeneity, thus the reduced performance compared to large commercial flocks was acceptable (Pirgozliev et al, 2016;Yang et al, 2020). It is possible that lighter birds may be less susceptible to heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…The relative empty weights of GIT segments including proventriculus, gizzard, small intestine and pancreas of each bird were also determined as previously described (Amerah and Ravindran, 2008;Pirgozliev et al, 2016). After that, approximately 5 cm of the middle part of the jejunum, between the point of bile duct entry and Meckel's diverticulum, of one of the birds was sampled and stored for 2 wk in 10% formalin-buffered saline.…”
Section: Gastrointestinal Tract Development and Ileal Villus Morphometrymentioning
confidence: 99%
“…Comparing mash vs pelleted diets, Pirgozliev et al (2016) found over 20% lower weight in birds fed mash diets, thus partially explaining the relatively low bird weight.…”
Section: Discussionmentioning
confidence: 89%